2017
DOI: 10.1155/2017/7430125
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm for Traveling Salesman Problem with Modified Cycle Crossover Operator

Abstract: Genetic algorithms are evolutionary techniques used for optimization purposes according to survival of the fittest idea. These methods do not ensure optimal solutions; however, they give good approximation usually in time. The genetic algorithms are useful for NP-hard problems, especially the traveling salesman problem. The genetic algorithm depends on selection criteria, crossover, and mutation operators. To tackle the traveling salesman problem using genetic algorithms, there are various representations such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 15 publications
0
69
0
2
Order By: Relevance
“…During the last three decades with the appearance of meta-heuristic algorithms, a new era of study about optimization problems and their applications has been started. These search algorithms have also been applied on TSP such as: particle swarm optimization [10], simulated annealing [11], ant colony optimization [12], neural network [13], tabu search [14], and genetic algorithms [15][16][17]. We also used GA in this research to solve the TSP.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last three decades with the appearance of meta-heuristic algorithms, a new era of study about optimization problems and their applications has been started. These search algorithms have also been applied on TSP such as: particle swarm optimization [10], simulated annealing [11], ant colony optimization [12], neural network [13], tabu search [14], and genetic algorithms [15][16][17]. We also used GA in this research to solve the TSP.…”
Section: Related Workmentioning
confidence: 99%
“…A profit-based genetic algorithm with TSP and obtaining good results to test on networks of cities of Poland was presented [19]. A comparative study of various crossovers with the modified form of cycle crossover operator for TSP was presented [17].…”
Section: Related Workmentioning
confidence: 99%
“…GAs are heuristic computing techniques that have been developed to find the best or near-best solution to optimization problems where the parameters are numerous and a theoretical approach is not suitable. Their application area is wide and includes engineering [20], traffic problems [21], medical applications such as radiology, radiotherapy, oncology and surgery [22]. This type of algorithm makes use of an abstract version of the Darwinian laws of genetics: a population of possible solutions, which are called chromosomes, is recombined randomly and evolves from a generation to the next through an iterative process.…”
Section: Introductionmentioning
confidence: 99%
“…www.ijacsa.thesai.org Further, we considered results reported in [37] for comparing with our proposed crossover ASCX. Recently Weise et al [38] made a comparative study among eleven crossover operators for the TSP and found that heuristic crossover (HX) [39] is the best performing operator.…”
mentioning
confidence: 99%
“…So, we implemented the GA using HX and run on the above twelve problem instances. It is to be noted that the same common parameters' values selected for GAs in [37] are used for ASCX and HX. The parameters are as follows: population size, maximum generation, crossover, and mutation probabilities are 150, 500, 0.80, and 0.10, respectively, for less than 100 size instances, whereas population size and maximum generation are 200 and 1000, respectively for more than 100 size instances.…”
mentioning
confidence: 99%